2021
DOI: 10.3389/fonc.2021.608987
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Signature in Melanoma: Biomarkers and Therapeutic Targets

Abstract: Melanoma is the utmost fatal kind of skin neoplasms. Molecular changes occurring during the pathogenic processes of initiation and progression of melanoma are diverse and include activating mutations in BRAF and NRAS genes, hyper-activation of PI3K/AKT pathway, inactivation of p53 and alterations in CDK4/CDKN2A axis. Moreover, several miRNAs have been identified to be implicated in the biology of melanoma through modulation of expression of genes being involved in these pathways. In the current review, we prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 290 publications
1
26
0
Order By: Relevance
“…Also, miRNAs are critical in many cellular processes in tumor cells, from differentiation and proliferation to death, and are tumor suppressor genes or oncogenes [ 3 ]. Numerous studies in SKCM have shown that miRNAs are aberrantly expressed, modulating proliferation, invasion, and metastasis of tumor cells [ 4 , 5 ]. Meanwhile, miRNAs not only are regulators for neoplasm biological characteristics but also influence tumor microenvironment (TME) and enhance immunotherapy response [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, miRNAs are critical in many cellular processes in tumor cells, from differentiation and proliferation to death, and are tumor suppressor genes or oncogenes [ 3 ]. Numerous studies in SKCM have shown that miRNAs are aberrantly expressed, modulating proliferation, invasion, and metastasis of tumor cells [ 4 , 5 ]. Meanwhile, miRNAs not only are regulators for neoplasm biological characteristics but also influence tumor microenvironment (TME) and enhance immunotherapy response [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the era of personalised medicine, the relationship between aberrant miRNA profile and response to therapeutic regimens should be further evaluated. Therapeutic targeting of miRNAs can impact the natural history of melanoma by enhancing sensitivity to both standard therapies and immune checkpoint inhibitors [189]. In particular, elevated levels of miRNA-221 have been identified in early melanomas, compared to healthy individuals.…”
Section: Micrornas (Mirnas) and Long Noncoding Rnas (Incrnas)mentioning
confidence: 99%
“…Not tumor specific and it is difficult to attribute whether changes in abundance are due to the cancer or to secondary conditions such as inflammation Droplet digital PCR [187][188][189][190][191][192][193][194][195][196] ctDNA: circulating tumor DNA; miRNAs: microRNAs; lncRNAs: long noncoding RNAs; UV: ultraviolet; LOH: loss of heterozygosity; PCR: Polymerase chain reaction; AS-PCR: allele-specific PCR; ARMS: allele-specific amplification refractory mutation system PCR; BEAMing: bead emulsification amplification and magnetics; NGS: next generation sequencing; Bi-PAP: mutation-specific bidirectional pyrophosphorolysis-activated polymerization.…”
Section: Micrornas (Mirnas) and Long Noncoding Rnas (Incrnas)mentioning
confidence: 99%
“…Despite a substantial genetic contribution, epigenetic heterogeneity and plasticity are crucial hallmarks associated with melanoma progression and resistance formation. In particular, changes in miRNAs have been associated with melanoma [9]. miRNAs are small ~21-24-nucleotide-sized non-coding RNAs that regulate gene expression by either inhibiting mRNA translation [10][11][12][13] or by causing RNA degradation [14][15][16], generally by binding to the 3 untranslated region (3 UTR) of mRNAs.…”
Section: Introductionmentioning
confidence: 99%